Fucoidan-Supplemented Diet Potentiates Immune Checkpoint Blockage by Enhancing Antitumor Immunity - Yang, Juan; Yang, Xianzhi; Pan, Wenfeng; Wang, Mingshuo; Lu, Yuxiong; Zhang, Jianeng; Fang, Ziqian; Zhang, Xiaomin; Ji, Yin; Bei, Jin-Xin; Dong, Jiajun; Wu, Yi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Immune checkpoint blockade (ICB) therapies such as PD-1 antibodies have produced significant clinical responses in treating a variety of human malignancies, yet only a subset of cancer patients benefit from such therapy. To improve the ICB efficacy, combinations with additional therapeutics were under intensive investigation. Recently, special dietary compositions that can lower the cancer risk or inhibit cancer progression have drawn significant attention, although few were reported to show synergistic effects with ICB therapies. Interestingly, Fucoidan is naturally derived from edible brown algae and exhibits antitumor and immunomodulatory activities. Here we discover that fucoidan-supplemented diet significantly improves the antitumor activities of PD-1 antibodies in vivo. Specifically, fucoidan as a dietary ingredient strongly inhibits tumor growth when co-administrated with PD-1 antibodies, which effects can be further strengthened when fucoidan is applied before PD-1 treatments. Immune analysis revealed that fucoidan consistently promotes the activation of tumor-infiltrating CD8+ T cells, which support the evident synergies with ICB therapies. RNAseq analysis suggested that the JAK-STAT pathway is critical for fucoidan to enhance the effector function of CD8+ T cells, which could be otherwise attenuated by disruption of the T-cell receptor (TCR)/CD3 complex on the cell surface. Mechanistically, fucoidan interacts with this complex and augments TCR-mediated signaling that cooperate with the JAK-STAT pathway to stimulate T cell activation. Taken together, we demonstrated that fucoidan is a promising dietary supplement combined with ICB therapies to treat malignancies, and dissected an underappreciated mechanism for fucoidan-elicited immunomodulatory effects in cancer.